Morphological Changes and Vascular Reactivity of Rat Thoracic Aorta Twelve Months After Pinealectomy - Kurcer, Zehra; Ozturk, Feral; Sahna, Engin; Kurus, Meltem; Olmez, Ercument (Ortadogu Ad Pres & Publ Co, 2010)
Objective: Melatonin, a hormone produced by the pineal gland, has been suggested to protect against development of hypertension and atherosclerosis. In this study, the effects of long-term melatonin deficiency for twelve months after pinealectomy on the alpha-adrenergic-contractions induced by phenylephrine, endothelium-dependent relaxation responses to acetylcholine and the morphological changes in the rat thoracic aorta were studied. Material and Metods: Rats were pinealectomized twelve months before the beginning of the vasomotor studies. Rings of arteries were mounted in isolated tissue baths for the measurements of isometric contractile force. The contractile responses to phenylephrine and endothelium-dependent relaxation responses to acetylcholine in the vessels were evaluated. Endothelial function was evaluated by vascular relaxation to acetylcholine. Histological examinations demonstrated the alterations of tunica media in the vessels of pinealectomized rats. Results: Thick and thin areas were observed in the transverse sections of vessels and the ratio of the widest media thickness to the narrowest was found significantly increased in pinealectomized group (2.85 +/- 056) when compared to the control group (1.65 +/- 0.10). In addition, alpha-smooth muscle actin and elastic lamellae staining of the media were attenuated in pinealectomized rats. Although contractile responses of vessels to phenylephrine in pinealectomized rats were lower than control group, significant difference was found for only one concentration (3x 10-8 mol l-1) of phenylephrine. There was no difference between the relaxation responses to acetylcholine in pinealectomized and control groups. Conclusion: These results show that long-term melatonin deficiency may cause some morphological changes in the tunics media of vessels. However, the function of endothelium and vascular responsiveness to proportional to-adrenergic stimulus seem to be mostly protected.
Pinealectomy pinealektomiden on İki ay sonra sıçanların torasik aortalarındaki morfolojik de?işiklikler ve vasküler reaktivite
Keywords: Melatonin; aorta, thoracic; rats